2021
DOI: 10.2174/2405520415666211229101553
|View full text |Cite|
|
Sign up to set email alerts
|

Natural Organic Matter (NOM) Transformations and their Effects on Water Treatment Process: A Contemporary Review

Abstract: One of the several significant concerns related to water treatment plants is the transformation of natural organic matter (NOM) concerning quality and quantity due to the changing climatic conditions. The NOM consists of heterogeneous functionalized groups. Phenolic and carboxyl groups are the dominant groups that are pH-dependent and show a stronger affinity towards the metals. Properties of natural organic matter and trace elements govern the binding kinetics, influencing cations' binding to functionalized g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…NOM is a poorly known heterogeneous mixture which derives from the degradation of bacteria, algae, and plant residuals and is ubiquitous in fresh waters . The concentrations of NOM in fresh water are up to 80 mg/L. , NOM contains aliphatic and aromatic moieties, e.g., carbonyl, carboxylic, amines, and phenolics, that may influence the oxidation of micropollutants. Studies on the hydroxyl radical (HO • ) based AOPs have shown the inhibitory effects of NOM on the abatement of micropollutants because of the high reactivity between HO • and NOM, of 10 8 –10 9 M –1 s –1 , and its moieties, e.g., phenol, of ∼10 10 M –1 s –1 . , As a consequence, HO • radicals are often consumed by NOM rather than reacting with the target micropollutants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOM is a poorly known heterogeneous mixture which derives from the degradation of bacteria, algae, and plant residuals and is ubiquitous in fresh waters . The concentrations of NOM in fresh water are up to 80 mg/L. , NOM contains aliphatic and aromatic moieties, e.g., carbonyl, carboxylic, amines, and phenolics, that may influence the oxidation of micropollutants. Studies on the hydroxyl radical (HO • ) based AOPs have shown the inhibitory effects of NOM on the abatement of micropollutants because of the high reactivity between HO • and NOM, of 10 8 –10 9 M –1 s –1 , and its moieties, e.g., phenol, of ∼10 10 M –1 s –1 . , As a consequence, HO • radicals are often consumed by NOM rather than reacting with the target micropollutants.…”
Section: Introductionmentioning
confidence: 99%
“… 17 The concentrations of NOM in fresh water are up to 80 mg/L. 18 , 19 NOM contains aliphatic and aromatic moieties, e.g., carbonyl, carboxylic, amines, and phenolics, that may influence the oxidation of micropollutants. Studies on the hydroxyl radical (HO • ) based AOPs have shown the inhibitory effects of NOM on the abatement of micropollutants because of the high reactivity between HO • and NOM, of 10 8 –10 9 M –1 s –1 , 20 and its moieties, e.g., phenol, of ∼10 10 M –1 s –1 .…”
Section: Introductionmentioning
confidence: 99%
“…Karnena et al, 2021 [86] reviewed the NOM characteristics and showed how the cations interact with the natural organic matter. Later Karnena et al, 2022 [87] removed the NOM from the wastewater using the coagulation techniques and stated that scaling up of studies are required for moving these techniques to be adopted by the water industry [88][89][90].…”
Section: Theory Of Coagulationmentioning
confidence: 99%